Regulación por hormonas tiroideas de genes de señalización involucrados en vías de sobrevida y proliferación en células de linfoma T - Cayrol, María Florencia (2015)
The interaction of lymphoid tumor cells with components of the extracellular matrix via the integrin ?v?3 allows tumor survival and growth. This integrin was demonstrated to be the membrane receptor for thyroid hormones in several tissues. We found that thyroid hormones (THs), acting as soluble integrin ?v?3 ligands, activated growth-related signaling pathways in T-cell lymphomas (TCL). In this work we show that physiological concentrations of THs acting through the integrin ?V?3 induced angiogenesis and proliferation of immature and mature TLC cells. We characterized the transcriptional program triggered upon the activation of the integrin ?V?3 by TH, that is ultimately linked to a NF-?B dependent mechanism that lead to the induction of angiogenic and cell proliferation genes such as VEGF. Moreover, we found that pharmacological inhibition of integrin ?V?3 reduces the proliferation of T-cell lymphomas in pre-clinical models, including patient-derived xenografts of ALCL tumors. In sum, we here show that integrin ?V?3 transduces pro-survival signals into TCL nuclei, suggesting a novel mechanism for the endocrine modulation of TCL pathophysiology. Targeting this mechanism could constitute an effective and potentially low-toxicity chemotherapy-free treatment for TCL patients.